Pengaruh Variasi Faktor Air Semen Terhadap Kinerja Mekanis Beton Bertulang - jernius setiaman zebua (Jurnal Sains, Teknik, Ekonomi, dan Pendidikan, 2026)
Reinforced concrete is a construction material widely used in infrastructure development due to its ability to withstand both compressive and tensile loads. The mechanical performance of reinforced concrete is strongly influenced by the concrete mix composition, particularly the water-cement ratio (w/c). This study aims to analyze the effect of variations in the water-cement ratio on the mechanical performance of reinforced concrete at curing ages of 7, 14, and 28 days. The water-cement ratios used in this study were 0.40, 0.45, 0.50, and 0.55. An experimental laboratory method was employed by producing reinforced concrete specimens and testing their mechanical performance using a compression testing machine. The results indicate that concrete with lower water-cement ratios exhibits higher mechanical performance compared to concrete with higher water-ccement ratios at all testing ages. Furthermore, the mechanical performance of concrete increases with curing age, with the highest values observed at 28 days. This study demonstrates that selecting an appropriate water-cement ratio plays a crucial role in improving the quality and mechanical performance of reinforced concrete, particularly for structural applications requiring high strength.